2016
DOI: 10.7150/ijms.16007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus on Radial and Ulnar Arterial Vasoreactivity after Radial Artery Cannulation: A Randomized Controlled trial

Abstract: Background: Endothelial dysfunction associated with diabetes mellitus (DM) may influence arterial vasoreactivity after arterial stimulus, such as cannulation, and cause changes in diameter and blood flow. Despite the frequent use of arterial cannulation during anesthesia and critical care, little information is available regarding vasoreactivity of the radial and ulnar arteries and its influence on underlying DM.Methods: Forty non-DM and 40 DM patients, who required arterial cannulation during general anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Therefore, the decrease in vessel lumen diameter of the catheterized artery may be associated with the increase in the flow velocity of the other artery in the same arm. With RA catheterization, the distal perfusion pressure of the capillary bed decreases, causing an increase in the pressure gradient between the UA and the capillary bed, resulting in increase of UA blood flow [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the decrease in vessel lumen diameter of the catheterized artery may be associated with the increase in the flow velocity of the other artery in the same arm. With RA catheterization, the distal perfusion pressure of the capillary bed decreases, causing an increase in the pressure gradient between the UA and the capillary bed, resulting in increase of UA blood flow [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that RA cannulation would decrease RA blood flow immediately after catheter placement and the compensatory increase in UA blood flow might quickly commence. Significant changes continued after 24 hours from the beginning of monitoring [18,21]. Zhenxian et al investigated the impact of transradial coronary procedures on the RA by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%